Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/ofid/ofz472
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Cardiovascular Disease Risk Profile of Tenofovir Alafenamide Versus Tenofovir Disoproxil Fumarate

Abstract: Background In human immunodeficiency virus (HIV) treatment, tenofovir alafenamide (TAF) is associated with greater increases in all fasting cholesterol subgroups compared with tenofovir disoproxil fumarate (TDF). Because lipid abnormalities may contribute to cardiovascular morbidity and mortality, cardiovascular risk assessment is integral to routine HIV care. This post hoc study evaluates the impact of lipid changes on predicted atherosclerotic cardiovascular disease (ASCVD) risk and statin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…36 In one randomized study of TAF versus TDF, cardiovascular safety end points were monitored for 96 weeks, including fasting lipids, proportion eligible for statin therapy, cardiovascular adverse events, and estimated 10-year atherosclerotic cardiovascular disease (ASCVD) risk. 37 No significant differences between groups were noted, except for the mean estimated 10-year ASCVD risk comparing TAF versus TDF (6.1% versus 6.2%; P = .04).…”
Section: Adverse Effects and Monitoringmentioning
confidence: 79%
“…36 In one randomized study of TAF versus TDF, cardiovascular safety end points were monitored for 96 weeks, including fasting lipids, proportion eligible for statin therapy, cardiovascular adverse events, and estimated 10-year atherosclerotic cardiovascular disease (ASCVD) risk. 37 No significant differences between groups were noted, except for the mean estimated 10-year ASCVD risk comparing TAF versus TDF (6.1% versus 6.2%; P = .04).…”
Section: Adverse Effects and Monitoringmentioning
confidence: 79%
“…41 A post hoc study evaluated the impact of lipid changes on predicted atherosclerotic cardiovascular disease (ASCVD) risk and statin eligibility in treatment-naïve 1774 adults living with HIV treated with TAF or TDF. 42 In that study, lipid changes (increases in total cholesterol, LDL and HDL) with TAF as part of co-formulated regimens did not substantively affect CVD risk profiles compared to TDF. However, considering the increasing age and other cardiovascular risk factors of patients living with HIV, changes in lipid parameters should be followed up closely and for the long term.…”
Section: Discussionmentioning
confidence: 72%
“…The elevation of biomarkers of lipids such as LDL-C was observed to have signi cance. Previous studies have also shown the elevation in the LDL-C and TG levels, but the range of elevation depended on the observational period, and the characteristics of the participants (17)(18)(19). One of the major risks for hyperlipidemia that was identi ed after switching to TAF was the elevation at beginning in TG or LDL-C levels (20) although opposite results also reported (21).…”
Section: Discussionmentioning
confidence: 95%